Estimation of Plankton Population Using Ensemble Kalman Filter - Kosala Dwidja Purnomo (Jurnal ILMU DASAR, 2008)
The objective of this paper is to simulate how the Ensemble Kalman Filter (EnKF) works to estimate plankton in the one-dimensional three components ecosystem model. The analysis has been done separately between nutrition component and plankton component. The simulation demonstrated that the EnKF with 100 ensembles has as good estimation as with 1000 ensembles. It will also be ilustrated that the increasing of ensemble size in EnKF can decrease the norm of error covariance of plankton component.